2023
DOI: 10.1038/s41368-022-00208-x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth number abnormality: from bench to bedside

Abstract: Tooth number abnormality is one of the most common dental developmental diseases, which includes both tooth agenesis and supernumerary teeth. Tooth development is regulated by numerous developmental signals, such as the well-known Wnt, BMP, FGF, Shh and Eda pathways, which mediate the ongoing complex interactions between epithelium and mesenchyme. Abnormal expression of these crutial signalling during this process may eventually lead to the development of anomalies in tooth number; however, the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 214 publications
(221 reference statements)
0
13
0
4
Order By: Relevance
“…Tooth agenesis was defined as missing 1 or more teeth from birth, excluding third molars. No differentiation among phenotypes was made because the correlation between agenesis of deciduous teeth (rare) and the permanent dentition (common) is very high, and number of missing teeth in heritable tooth agenesis can vary considerably even within families . Data on tooth agenesis were obtained from 2 different national registries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tooth agenesis was defined as missing 1 or more teeth from birth, excluding third molars. No differentiation among phenotypes was made because the correlation between agenesis of deciduous teeth (rare) and the permanent dentition (common) is very high, and number of missing teeth in heritable tooth agenesis can vary considerably even within families . Data on tooth agenesis were obtained from 2 different national registries.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Several causative genes have also been identified for isolated (nonsyndromic) tooth agenesis, which can present with variable phenotypes, even within families. 3,5 Variants in some genes, such as WNT10A (OMIM 150400) and EDA (OMIM 300451), can present as both syndromic and nonsyndromic tooth agenesis. 4 Previous reports have suggested that individuals with tooth agenesis may have an increased risk of developing certain cancer types, as some of the cellular signaling pathways important for tooth formation also play a role in cancer development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…USAG-1(uterine sensitization associated gene-1), expressed predominantly in the kidneys, inhibits BMP-7's bioactivity which is crucial for tooth development. [6][7][8][9][10][11][12] By way of knocking out the gene Usag-1, tooth regeneration has been shown. Hence, inhibition of Usag-1 may provide a way for teeth regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous studies have focused on the regulatory role of EDA in epithelial development including that of teeth and hair. 8,9 It should be noted that in ectodermal dysplasia there are disorders of epithelial-mesenchymal interactions affecting the structure of the endoderm and ectoderm, which are not confined to a single ectoderm. 10 The mandibular morphology was abnormal in EDA −/− mice (Tabby mice, a mouse model of XLHED), which showed the lower corpus of the jaw, narrower neck of the condyle, and marked backward projection of the coronoid process.…”
Section: Introductionmentioning
confidence: 99%